Effects of the crystal phase and microstructure of pottery bodies on the transmission characteristics of terahertz waves. Issue 2 (3rd April 2021) - Niijima, Seiji; Taniguchi, Hiroaki; Matsuda, Hideki; Hashimoto, Noritsugu; Murate, Kosuke; Kawase, Kodo
ABSTRACT: We recently reported that the terahertz (THz)-wave characteristics of pottery bodies varied significantly with firing temperature. This suggested the feasibility of conducting nondestructive inspection of the sinterability and manufacturing-process management of ceramics by THz-wave analysis. However, it is not clear why the THz-wave characteristics of ceramics change with firing temperature. In this study, we evaluated the THz-wave transmission properties of low-temperature-sintered porcelain bodies fired at various temperatures using THz time-domain spectroscopy and investigated the relationship between the crystal phase and microstructure. We found that the THz-wave transmittance increased with the dehydration of kaolinite and decreased with the formation of mullite and glass phases in the body. Also, as the firing temperature increased, the THz-wave transmittance of these bodies was affected by scattering due to the formation of pores. Additionally, the refractive index in the THz range showed a good correlation with the bulk density. We established that the firing-temperature dependence of the refractive index in the THz range was related to the crystal phase and microstructure.